Correlates and determinants of Early Infant Diagnosis outcomes in North-Central Nigeria - Patrick Dakum; Monday Tola; Nta Iboro; Chukwuemeka A. Okolo; Olachi Anuforom; Christopher Chime; Sam Peters; Jibreel Jumare; Obinna Ogbanufe; Aliyu Ahmad; Nicaise Ndembi (AIDS Research and Therapy, 2019)
Abstract Background A negative status following confirmatory Early Infant Diagnosis (EID) is the desired pediatric outcome of prevention of Mother to Child Transmission (PMTCT) programs. EID impacts epidemic control by confirming non-infected HIV-exposed infants (HEIs) and prompting timely initiation of ART in HIV-infected babies which improves treatment outcomes. Objectives We explored factors associated with EID outcomes among HEI in North-Central Nigeria. Method This is a cross-sectional study using EID data of PMTCT-enrollees matched with results of HEI’s dried blood samples (DBS), processed for DNA-PCR from January 2015 through July 2017. Statistical analyses were done using SPSS version 20.0 to generate frequencies and examine associations, including binomial logistic regression with p < 0.05 being statistically significant. Results Of 14,448 HEI in this analysis, 51.8% were female and 95% (n = 12,801) were breastfed. The median age of the infants at sample collection was 8 weeks (IQR 6–20), compared to HEI tested after 20 weeks of age, those tested earlier had significantly greater odds of a negative HIV result (≤ 6 weeks: OR = 3.8; 6–8 weeks: OR = 2.1; 8–20 weeks: OR = 1.5) with evidence of a significant linear trend (p < 0.001). Similarly, HEI whose mothers received combination antiretroviral therapy (cART) before (OR = 11.8) or during the index pregnancy (OR = 8.4) had significantly higher odds as compared to those whose mothers did not receive cART. In addition, HEI not breastfed had greater odds of negative HIV result as compared to those breastfed (OR = 1.9). Conclusions cART prior to and during pregnancy, earlier age of HEI at EID testing and alternative feeding other than breastfeeding were associated with an increased likelihood of being HIV-negative on EID. Therefore, strategies to scale-up PMTCT services are needed to mitigate the burden of HIV among children.